Dopamine D2-Subtype Receptors Outside the Blood-Brain Barrier Mediate Enhancement of Mesolimbic Dopamine Release and Conditioned Place Preference by Intravenous Dopamine - Obray, J. Daniel; Small, Christina A.; Baldwin, Emily K.; Jang, Eun Young; Lee, Jin Gyeom; Yang, Chae Ha; Yorgason, Jordan T.; Steffensen, Scott C. (Frontiers in Cellular Neuroscience, 2022)
Dopamine (DA) is a cell signaling molecule that does not readily cross the blood brain barrier. Despite this, peripherally administered DA enhances DA levels in the nucleus accumbens and alters DA-related behaviors. This study was designed to investigate whether DA subtype-2 receptors are involved in the enhancement of nucleus accumbens (NAc) DA levels elicited by intravenous DA administration. This was accomplished by using microdialysis in the NAc and extracellular single unit recordings of putative DA neurons in the ventral tegmental area (VTA). Additionally, the reinforcing properties of intravenous DA were investigated using a place conditioning paradigm and the effects of intravenous DA on ultrasonic vocalizations were assessed. Following administration of intravenous dopamine, the firing rate of putative DA neurons in the VTA displayed a biphasic response and DA levels in the nucleus accumbens were enhanced. Pretreatment with domperidone, a peripheral-only DA D2 receptor (D2R) antagonist, reduced intravenous DA mediated increases in VTA DA neuron activity and NAc DA levels.. Pretreatment with phentolamine, a peripheral α-adrenergic receptor antagonist, did not alter the effects of IV DA on mesolimbic DA neurotransmission. These results provide evidence for peripheral D2R mediation of the effects of intravenous DA on mesolimbic DA signaling.